Efektivitas Leaflet Terhadap Pengetahuan Kader tentang Pemberian Makan Bayi dan Anak (PMBA) untuk Pencegahan Stunting - Susanti Tria Jaya (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
Stunting is a condition of failure to thrive in children under five years of age (toddlers) due to chronic malnutrition which is characterized by below standard length or height. The proportion of stunting in Indonesia reached 24.4%. Stunting can inhibit physical growth, increase children's susceptibility to disease, cause cognitive development barriers that reduce children's intelligence and productivity in the future, and will increase the risk of degenerative diseases in adulthood. The purpose of this study was to analyze the Effectiveness of Using Leafleat Media on Posyandu Cadres' Knowledge of PMBA for Stunting Prevention in January 2022. The method used was a pre and post one group design with 30 posyandu cadre respondents in Jajar Village. The results obtained from this study were an increase in knowledge before and after the intervention, namely the information provided in the leaflets media. The conclusion of the study is that the information in the leaflet is beneficial for increasing the knowledge of posyandu cadres about PMBA for stunting prevention.